Strategic Alignment and Institutional Resilience in China–Pakistan Bilateralism - Saoud Ahmed; Muhammad Aquib (Dialogium: Journal of Islamic Studies, 2026)
China–Pakistan bilateralism represents a strategically significant partnership within the shifting great power nexus, characterized by political trust, economic integration, and institutionalized cooperation. This study aims to examine how strategic agency and institutional coordination jointly sustain the durability of this bilateral relationship, addressing the gap in literature that often treats strategy and institutions separately. A qualitative comparative research design was employed, using document analysis of official agreements, policy frameworks, government reports, and academic studies conducted between January and June 2025. The analysis focused on political, economic, and security sectors to identify patterns of decision-making and coordination. Findings indicate that both states actively exercise strategic agency while relying on formal and informal institutions to translate strategic objectives into sustained outcomes, including policy continuity, sectoral cooperation, and strategic stability. Economic initiatives, especially infrastructure and connectivity projects, demonstrate higher institutional formalization compared to security cooperation, reflecting functional requirements rather than differences in commitment. The study concludes that the resilience of China–Pakistan bilateralism arises from the mutual reinforcement of strategic agency and institutional coordination, highlighting that effective bilateral partnerships require the integration of strategy, governance, and shared norms. These findings contribute to understanding bilateralism, great power dynamics, and institutional governance in international relations.